(untitled) (International Journal of Physiotherapy, 2025)
Background: In Saudi Arabia, stroke incidence is 29.8 cases per 100,000 inhabitants annually, and Hemiplegic shoulder pain (HSP) is a prevalent issue after stroke, affecting approximately 47% of patients with stroke. This study aimed to assess physiotherapists’ knowledge, attitudes, and practices toward Hemiplegic Shoulder Pain (HSP) management in Saudi Arabia. Methods: This cross-sectional study included 523 physiotherapists who treated patients with stroke between August and November 2023 in Saudi Arabia. An online survey was administered to the physiotherapists. The questionnaire comprised four main parts, covering sociodemographic characteristics, participants’ knowledge, attitudes, and current practices regarding HSP, HSP assessment, and HSP management. Results: A total of 300 (57.63%) participants responded. The results showed that 48% of the participants treated 1–5 patients with stroke in their daily practice. In addition, 46.3% of the participants reported that up to 75% of the patients with stroke they treated experienced HSP. Furthermore, the most commonly used interventions to manage HSP were repetitive task-specific practice, functional strengthening exercises, and range of motion exercises. A notable correlation was observed between the participants’ educational level and experience and their responses regarding their knowledge and attitudes toward HSP. Conclusion: Physiotherapists in Saudi Arabia demonstrated positive attitudes, knowledge, and practices toward HSP rehabilitation. The complex challenges related to HSP rehabilitation highlight the importance of sharing knowledge and information, teamwork, and up-to-date exercise practices for the effectiveness of HSP rehabilitation.